Hubungan Sanitasi Lingkungan dan PHBS dengan Kejadian Stunting pada Balita Usia 12-59 Bulan - Aulia Dwi Wulandani; Krisdiana Wijayanti; Rafika Fajrin (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2025)
Stunting remains a significant public health issue in Indonesia, as its national prevalence exceeds WHO standards. Purworejo Regency, located in Central Java, is among the areas prioritized for poverty and stunting reduction efforts. This research aimed to analyze the correlation between environmental sanitation, Clean and Healthy Living Behavior (PHBS), and stunting among children aged 12–59 months within the Grabag Health Center area. Using a quantitative case-control design, the study involved 104 respondents, consisting of 52 cases and 52 controls. Data were analyzed using the chi-square test and odds ratio (OR). he findings demonstrated a significant link between environmental sanitation and stunting (p < 0.05, OR = 6.296), indicating that children residing in unhygienic surroundings were over six times more likely to experience stunting. A significant association was also found between poor PHBS and stunting (p = 0.000, OR = 10.360), indicating a tenfold increased risk. Based on these findings, it is recommended that health workers, particularly midwives, collaborate with posyandu (integrated health post) cadres to enhance parental knowledge through education on the importance of proper environmental sanitation and PHBS, in order to protect children from stunting and related health risks.